Uma defesa do discurso libertarista de Alvin Plantinga frente ao ateísmo analítico contemporâneo. - Santana, Marcílio Monteiro de (2022)
The aim of this dissertation is to investigate the plausibility of Alvin Plantinga's possible libertarianism, as it relates to the logical argument from evil, the epistemic justification of theistic beliefs and the debate about the coherence of theism. For this, a review will be made of some fundamental themes of Plantinga's theoretical position, insofar as they reflect the arguments in favor of a possible libertarian conception of freedom; this conception being an important presupposition of the argument that defends the coherence of theism. As an argumentative counterpoint, we will present Michael Tooley's probabilistic objection, which proposes a new version of the argument from evil, as a way of invalidating Plantinga's Defense of Free Will, taking analytical atheism as its starting point. We will argue that the plantinganian libertarian position is plausible in what it proposed: to demonstrate that there is no logical incompatibility between the concept of God and the occurrence of unwanted states of affairs (moral evil), that such states of affairs would result from the inappropriate use of libertarian free will, and that Plantinga's notion of libertarian freedom does not imply randomness, with regard to the origin of human actions. In this way, the plantinganian libertarian argument succeeds against the objection of analytical atheism.